Pertanggungjawaban Marketplace Shopee Terhadap Peredaran Obat Pelangsing Tanpa Izin Edar Perspektif Fatwa DSN-MUI Nomor 146 Tahun 2021 Tentang Online Shop Berdasarkan Prinsip Syariah - Anasta, Qhadizah; Sativa, Annisa (Dinasti Review Publisher, 2024)
This research evaluates Shopee's responsibility regarding the circulation of unauthorized slimming drugs, focusing on the perspective of the Indonesian Council of Ulama (MUI) Fatwa Number 146 of 2021 on Online Shops. In the context of the circulation of illegal drugs, Shopee face challenges in quality control and product safety on its platform. It was found that the Indonesian Food and Drug Authority (BPOM) discovered thousands of illegal drug packages on Shopee, raising questions about the effectiveness of preventive measures and the accountability of the Shopee marketplace from the perspective of MUI Fatwa Number 146 of 2021. Using a normative juridical approach, this study employs the statutes approach, conceptual approach, and comparative analysis to assess Shopee's compliance with Sharia principles in the context of online buying and selling. The research results indicate that Shopee has adhered to the principles of the fatwa, involving a firm contractual process, prohibition of actions contrary to Sharia principles, and the removal of illegal content. The importance of collaboration between marketplaces and health authorities, such as BPOM, is also recognized to enhance control and consumer protection regarding illegal slimming drug products